Exploring the origin of the cancer stem cell niche and its role in anti-angiogenic treatment for glioblastoma - Akindona, Funto A.; Frederico, Stephen C.; Hancock, John C.; Gilbert, Mark R. (Frontiers in Oncology, 2022)
Cancer stem cells are thought to be the main drivers of tumorigenesis for malignancies such as glioblastoma (GBM). They are maintained through a close relationship with the tumor vasculature. Previous literature has well-characterized the components and signaling pathways for maintenance of this stem cell niche, but details on how the niche initially forms are limited. This review discusses development of the nonmalignant neural and hematopoietic stem cell niches in order to draw important parallels to the malignant environment. We then discuss what is known about the cancer stem cell niche, its relationship with angiogenesis, and provide a hypothesis for its development in GBM. A better understanding of the mechanisms of development of the tumor stem cell niche may provide new insights to potentially therapeutically exploit.